2020
DOI: 10.1177/1558925020978652
|View full text |Cite
|
Sign up to set email alerts
|

Natural flat cocoon materials constructed by eri silkworm with high strength and excellent anti-ultraviolet performance

Abstract: Eri silkworm is easy to be raised and has high cocoon yield, the cocoon fails to be continuously reeled due to a loose structure, a large part of cocoon coat and an eclosion hole. In this work, a fifth instar larvae of eri silkworm was provided with only a flat cocooning place to spin to produce a flat cocoon, it was fed with the castor leaves sprayed with nano-TiO2 and graphene oxide (GO), Compared with the flat cocoon obtained without nanomaterials, the silk was not found to change in morphology and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The results revealed that the modified silk fabric exhibited more than a 60-fold increment in the UPF value that reached 445 compared to the silk fabric (Table 1) [38]. Another attempt conducted by Bin Zhou et al found that spraying castor leaves with GO and TiO 2 nanoparticles individually on silk textile fabrics enhances the UV protection ability significantly [17]. This is due to the ability of GO and the TiO 2 nanoparticles for blocking UV rays by different means.…”
Section: Graphene-based Coatingsmentioning
confidence: 95%
See 2 more Smart Citations
“…The results revealed that the modified silk fabric exhibited more than a 60-fold increment in the UPF value that reached 445 compared to the silk fabric (Table 1) [38]. Another attempt conducted by Bin Zhou et al found that spraying castor leaves with GO and TiO 2 nanoparticles individually on silk textile fabrics enhances the UV protection ability significantly [17]. This is due to the ability of GO and the TiO 2 nanoparticles for blocking UV rays by different means.…”
Section: Graphene-based Coatingsmentioning
confidence: 95%
“…where E λ refers to the relative erythemal spectral effectiveness (the action spectrum), S λ is the solar UV spectral irradiance for a typical summer period during midday in clear sky conditions, d λ indicates the increment in the wavelength, λ represents the wavelength (nm), and T λ is the spectral transmittance of the specimen determined by the UV/Vis spectrophotometer equipment [16,17]. The uncertainty of measurement mainly depends on the accuracy and precision of the spectrophotometer used, as these vary from one to another.…”
Section: Textile Fabric Coatings For Uv Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild cocoons live outdoors, and their sericin content is higher [14][15][16][17]. The sericin content is as high as 15% to 25% in the cocoon coat, which is also associated with their better protection against UV rays to ensure the normal development of silkworm larvae [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of FSC include a controllable size, excellent mechanical properties, and porous layer structure. Although few studies have reported on the use of FSC in the field as a biological material, particularly for the healing of wounds, it has demonstrated significant advantages as a composite matrix ( Zhou et al, 2020 ) ( Figure 1 ). In addition, silk (including sericin) can effectively promote the regeneration of wound tissues with its great biocompatibility and antibacterial and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%